Inverse Kinematics Analysis of Six-degree-of-freedom Mechanism for Wind Tunnel Capture Trajectory - Ning Li; Zhijiang Xie; Anlin Jiang; Lisheng Mou; Liou Hu (Jixie chuandong)
A series of six-degree-of-freedom mechanism is proposed for the needs of wind tunnel capture trajectory experimental equipment. The kinematics positive solution model of the mechanism is established. For the problem of the inverse kinematics of the series mechanism， the inverse kinematics of this mechanism is explored by BP neural network and numerical method. In the face of the problem that the initial value estimation is difficult when the inverse method of numerical method is solved， a new method is proposed. The correctness of the method is verified by an example analysis. The problem of initial value estimation when solving numerical method is solved， which makes the numerical method solve the inverse solution smoothly. Compared with BP neural network， the numerical method has higher precision.